2019
DOI: 10.3892/ol.2019.10366
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the survival of patients with lung adenocarcinoma using a four‑gene prognosis risk model

Abstract: Lung adenocarcinoma (LAD) is difficult to diagnose as it tends to be small in size and metastasize early. The aim of the present study was to investigate prognostic factors for patients with LAD and establish a prognosis risk model. A training set consisting of clinical and RNA sequencing data from 503 patients with LAD, as well as expression data from a further 59 LAD and adjacent tissues, was obtained from The Cancer Genome Atlas. Additionally, a validation dataset was acquired from the Gene Expression Omnib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…However, little research has been done on the relationship between ERO1L and tumors, and the existing research was limited to prognostic correlations 31,32 . In our study, ERO1L was closely related to the prognosis of lung adenocarcinoma which was consistent with literature reports 33 . The use of multiple markers for diagnosis can avoid the shortcomings of a single marker.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, little research has been done on the relationship between ERO1L and tumors, and the existing research was limited to prognostic correlations 31,32 . In our study, ERO1L was closely related to the prognosis of lung adenocarcinoma which was consistent with literature reports 33 . The use of multiple markers for diagnosis can avoid the shortcomings of a single marker.…”
Section: Discussionsupporting
confidence: 93%
“…It has been reported that high expression of ERO1L in a variety of tumors including breast, gastric, esophageal, and pancreatic cancer is associated with poor prognosis [16][17][18][19][20][21] . ERO1L is included in various prognostic models of lung adenocarcinoma 22,23 . However, there are few studies on the mechanism by which ERO1L affects prognosis, and its relationship with specific secreted proteins needs further study.…”
Section: Introductionmentioning
confidence: 99%
“…Later, additional biological functions, such as insulin biogenesis and glucose homeostasis, were demonstrated [51]. In relation to lung cancer, ERO1B has been recently identified as a gene that, together with an additional three genes identified using TCGA LUAD dataset, is able to predict patient prognosis [52] and has been suggested to be a biomarker for pancreatic cancer [53,54]. DPY19L1 was firstly identified as an unclassified gene from human brain cDNA libraries in 1998 [55].…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al studied the expression of 4 genes, MYO1E , ERO1L , C1QTNF6 , and FAM83A , to build a prognostic panel for lung cancer. Functional enrichment analysis indicated that dysfunction in these genes are involved in regulation and progression of the cell cycle, synthesis and assembly of nucleic acids, and histone modification [ 23 ]. Lee et al suggested a positive correlation of FAM83A with therapeutic resistance of tyrosine kinase inhibitors in breast cancer.…”
Section: Discussionmentioning
confidence: 99%